2019
DOI: 10.1007/s10956-019-9770-8
|View full text |Cite
|
Sign up to set email alerts
|

Collection-Based Education by Distance and Face to Face: Learning Outcomes and Academic Dishonesty

Abstract: Assembling and curating specimen collections is a valuable educational exercise that integrates subject-specific skills such as field collection, curation, identification, organization, and interpretation of relationships. Collection projects have been used primarily in face-to-face classes, but they can be readily adapted for distance education. The primary challenges to using collection projects in distance education center on two concerns: (1) whether distance students learn as much as their face-toface pee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 25 publications
0
8
0
1
Order By: Relevance
“…In contrast, online education could lead instructors and students to resort to unethical plagiarism (Ubell, 2017). Lucky et al (2019) discussed that the rate of students who resort to academic fraud in online education (distance education) was 12 times higher than the rate in face-to-face education. Furthermore, according to certain studies, there was no significant difference between learning outcomes in online and face-to-face education (Allen & Seaman, 2010;Allen et al, 2002;Biner et al, 1995;Brown & Liedholm, 2002).…”
Section: Online-distance Educationmentioning
confidence: 99%
“…In contrast, online education could lead instructors and students to resort to unethical plagiarism (Ubell, 2017). Lucky et al (2019) discussed that the rate of students who resort to academic fraud in online education (distance education) was 12 times higher than the rate in face-to-face education. Furthermore, according to certain studies, there was no significant difference between learning outcomes in online and face-to-face education (Allen & Seaman, 2010;Allen et al, 2002;Biner et al, 1995;Brown & Liedholm, 2002).…”
Section: Online-distance Educationmentioning
confidence: 99%
“…Standards, Plagiarism and Academic Dishonesty. Although educational researchers found that students who took online classes were less likely to cheat as compared with the students who took face-to-face courses [10,11], keeping the academic integrity in a "virtual classroom" remains an open problem for online teaching. For computing courses, such as computer science/programming, there is enough available material online such as Wikipedia, blogs and forums, and of course YouTube, where most traditional course material can be found expeditiously.…”
Section: Resultsmentioning
confidence: 99%
“…Of course, scientists, teachers and managers in the education sector confirmed the role of the distance learning form in studying the law (Wu, 2015;Lucky, Branham & Atchison, 2019;Muilenburg & Berge, 2005). Therefore, practical scientific activity may be unfolded using distance courses that are significant.…”
Section: Background and Research Questionsmentioning
confidence: 96%